Potential of Boronic Acid Derivatization and Activity in Agrochemical Discovery - Liangshuo Ji; Jianxin Wu; Yachen Zuo; Wenqiang Gao; Jiyao Feng; Zhenhua Zhang (Molecules)
Since the approval of Bortezomib (Velcade®) by the U.S. Food and Drug Administration (FDA) in 2003, boron-containing drugs have successfully entered the global market, spanning therapeutic areas such as anticancer, antibacterial, and antifungal agents. Meanwhile, boron is an essential trace element for plant growth, and boronic acid has been widely used as plant resistance inducers and growth promoters. In 2024, the Fungicide Resistance Action Committee (FRAC) introduced benzoxaboroles as a new category of fungicides, which fully demonstrates the significant application potential of boron-containing compounds (BCCs) in the field of agricultural fungicides. Recently, studies on BCCs in agriculture have emerged continuously. Compared with the systematic reviews in the pharmaceutical field, those focusing on BCCs in agriculture remain absent. This review systematically collates BCCs with reported biological activities from the literature over the past 20 years, from the perspective of boron-containing building blocks. It mainly focuses on the potential of boronic acid derivatization and its activities in agrochemicals. Additionally, it covers the applications of boron-containing building blocks in pharmaceuticals, including their action mechanisms.